THE INTERPLAY BETWEEN AGRICULTURE AND BIODIVERSITY: A CRITICAL EXAMINATION - Gupta, Gauri; Kumar, Amit (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Agriculture and biodiversity are intricately linked, influencing each other in profound ways. This paper explores the relationships between agricultural practices and biodiversity across various ecosystems, highlighting both the positive and negative impacts of agricultural systems on biological diversity. It examines sustainable agricultural practices that promote biodiversity and discusses the role of policy and management in fostering a harmonious coexistence. By analysing case studies from different regions, the paper aims to provide insights into the ways agriculture can support or hinder biodiversity, ultimately suggesting pathways for more sustainable agricultural practices.